"A STUDY AND SYSTEMATICAL ANALYSIS OF ENTREPRENEURIAL PROCESS AND BUSINESS OPPORTUNITIES" - Mohan Alex Medayil; R. S. Balakumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
In the past few decades, entrepreneurship has become a very popular topic for both educational academicians and policy makers for the specific role of national economic and social development. Indeed, it can tackle the current economic crisis that stimulates innovation and technological progress, creates competition, creates jobs, and promotes general economic growth. Entrepreneurs are change agents who act as entrepreneurs and assume the risks associated with the formation of a business for commercial use. A company has an unusual vision that characterizes the potential demand for a product or service. There are several specific steps to understanding or following every topic and every method you’ve learned so far. From the very basics of a topic or application section to its more advanced usage and requirements, it all follows a few specific steps. Entrepreneurship also depends in part on the methodology of fostering entrepreneurs, and each of these terms also has a specific function.